Organizational Characteristics of Hospitals Meeting STRIDE Program Adoption Benchmarks to Support Mobility for Hospitalized Persons - Leah L. Zullig PhD, MPH; Connor Drake PhD; Amy Webster BS; Matthew Tucker BA; Ashley Choate MPH; Karen M. Stechuchak MS; Cynthia J. Coffman PhD; Caitlin B. Kappler MSW; Cassie Meyer BS; Courtney H. Van Houtven PhD; Kelli D. Allen PhD; Jaime M. Hughes PhD, MPH, MSW; et al. (Inquiry: The Journal of Health Care Organization, Provision, and Financing, 2024)
There are few validated contextual measures predicting adoption of evidence-based programs. Variation in context at clinical sites can hamper dissemination. We examined organizational characteristics of Veterans Affairs hospitals implementing STRIDE, a hospital walking program, and characteristics’ influences on program adoption. Using a parallel mixed-method design, we describe context and organizational characteristics by program adoption. Organizational characteristics included: organizational resilience, implementation climate, organizational readiness to implement change, highest complexity sites versus others, material support, adjusted length of stay (LOS) above versus below national median, and improvement experience. We collected intake forms at hospital launch and qualitative interviews with staff members at 4 hospitals that met the initial adoption benchmark, defined as completing supervised walks with 5+ unique hospitalized Veterans during months 5 to 6 after launch with low touch implementation support. We identified that 31% (n = 11 of 35) of hospitals met adoption benchmarks. Seven percent of highest complexity hospitals adopted compared to 48% with lower complexity. Forty-three percent that received resources adopted compared to 29% without resources. Thirty-six percent of hospitals with above-median LOS adopted compared to 23% with below-median. Thirty-five percent with at least some implementation experience adopted compared to 0% with very little to no experience. Adopters reported higher organizational resilience than non-adopters (mean = 23.5 [SD = 2.6] vs 22.7 [SD = 2.6]). Adopting hospitals reported greater organizational readiness to change than those that did not (mean = 4.2 [SD = 0.5] vs 3.8 [SD = 0.6]). Qualitatively, all sites reported that staff were committed to implementing STRIDE. Participants reported additional barriers to adoption including challenges with staffing and delays associated with hiring staff. Adopters reported that having adequate staff facilitated implementation. Implementation climate did not have an association with meeting STRIDE program adoption benchmarks in this study. Contextual factors which may be simple to assess, such as resource availability, may influence adoption of new programs without intensive implementation support.